Stabilization (Precipitation) Of Mercury From Precious Metals Extraction Wastes Utilizing Trimercaptotriazine - Ljiljana Solujic (The Minerals, Metals and Materials Society, 1996)
The need for the removal of mercury from the precious metals extraction circuits may be influenced by process, environmental, as well as by occupational hazard reasons. In these circuits mercury is mainly present as cyanide complexes. The effectiveness of any stabilization method will be influenced by the high thermodynamic stability mercury-cyano species exhibit in an aqueous solution. In this study, we have investigated the utility of the trisodium salt of trimmercapto-s-triazine (TMT) for precipitation of mercury from the corresponding cyano-complexes. The influence of pH molar ratio of TMT to Hg, coagulant and flocculant additions, excess of free cyanide, as well as the presence of other metal-cyano species on the effectiveness of mercury precipitation were investigated in detail. Also, a "teal world" precious metals mill effluent initially containing ~7 ug/mL (ppm) of Hg was treated and A was found that greater than 99.8% of the mercury was removed from the solution as am insoluble Hg/TMT complex.